Analysis of Modality in EFL Textbooks for Junior High School Students - Syafrayani, Putri Rizki (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study explores modality in English as a Foreign Language (EFL) textbooks, addressing a gap in prior research that emphasizes modal verbs’ frequency over their functional use. It analyzes the types and realization of modality in the Indonesian junior high school textbook English for Nusantara Grade VII using Halliday’s Systemic Functional Linguistics framework. Data, sourced from exercises, dialogues, and passages, were categorized into modalization (probability and usuality) and modulation (obligation and inclination). Findings indicate a prevalence of medium modality, with "can" and "should" frequently used, reflecting moderate obligation and possibility. The textbook prioritizes expressing ability and certainty over obligation, suggesting the need for more balanced instructional material. This study underscores the importance of integrating practical exercises that teach nuanced modality use, enhancing students' ability to communicate effectively in real-world contexts. Aligning with language's interpersonal function, such improvements could foster socially appropriate and meaningful exchanges in English. Keyword : EFL textbooks, Halliday and Matthiessen framework, Modalization, Modulation.